Peran Akuntansi Manajemen Lingkungan dalam Memediasi Inovasi Ramah Lingkungan pada Nilai Perusahaan Terhadap Perusahaan di BEI - Nadya Sari; Rilla Gantino (Owner : Riset dan Jurnal Akuntansi, 2022)
This research is about the role of environmental management accounting in mediating green innovation by using CSR disclosure on firm value. This study uses manufacturing companies in the basic and chemical industry sub-sectors listed on the IDX in 2017 – 2019 because these sub-sectors have a more significant influence on environmental pollution. The population of this study is manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2017-2019, totaling 71 companies and the research sample as many as 46 companies using the purposive sampling method. This study uses a quantitative method with a descriptive approach. The results show that green innovation affects environmental management accounting and directly affects firm value. Environmental management accounting now has a significant influence on firm value. Environmental management accounting cannot mediate between green innovation and company value in basic and chemical industrial sector companies listed on the IDX.